Konsep Kesetaraan Pasangan dalam Pernikahan Pandangan Wahbah Az-Zuhaili dalam Tafsir Nya (Analisis Qs. An-Nur Ayat 26) - Ifrohul Fadhilah; Hasan Bakti Nasution (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This article discusses the concept of equality of partners in marriage according to the views of Wahbah az-Zuhaili through the interpretation of the QS. An-Nur verse 26 in his tafsir al-Munīr. This verse emphasizes the reciprocal relationship between the moral qualities of an individual and his life partner, that "a good woman is for a good man, and a good man is for a good woman", which is substantially understood by az-Zuhaili as the principle of moral harmony and equality in human values ​​between husband and wife. This study aims to analyze how az-Zuhaili interprets equality not only as moral equality, but also as the basis for household harmony from a sharia perspective. The research method used is literature study by examining in depth the tafsir of al-Munīr, the works of az-Zuhaili fiqh, as well as relevant literature regarding family ethics in Islam. The results of the analysis show that Wahbah az-Zuhaili understands this verse as an affirmation that ideal marriage is based on moral compatibility, purity of behavior, and equality of dignity between partners. According to him, equality does not mean eliminating the roles of each party, but rather positioning husband and wife as two individuals who complement each other in goodness, responsibility, and mutual respect. This verse is also understood as a critique of cultures that demean women or make them objects of moral stigma. Thus, az-Zuhaili's thinking, through an analysis of Surah An-Nur verse 26, provides the perspective that spousal equality in Islam is rooted in the principles of noble morals and a balance of rights and obligations, which are the foundation for building a harmonious family and an ethical society.